Pattern and Management Outcomes of Chest Wall Fractures with Associated Orthopedic Injuries in Polytrauma Patients at a Tertiary Care Hospital in Pakistan - Nasir Hussain, Safdar Iqbal, Mian Sami Azhar, Aamer Wadud, Muhammad Farooq, Arsalan Siraj, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Chest wall fractures constitute amajor contributor to morbidity and mortality in polytrauma, particularly whenaccompanied by orthopedic injuries